TANTANGAN MENCIPTAKAN KEUNGGULAN KOMPETITIF DENGAN PENILAIAN KINERJA YANG KOMPREHENSIF - Rahadhini, M.D . (Universitas Slamet Riyadi, 2010)
Abstract The critical factor that relates to the succees of organization in long-term is its ability to measure how good its employees are in working and using information to make sure that the implementation of appraisal has fullfilled the standard and increased better along the way. Performance appraisal is a proper means in evaluating and developing also in motivating employees. Performance appraisal can be the way to help person in managing their performance. But appraisal has to be done in certain method and technique that is adjusted to the situation and condition of organization, such as culture of organization. It must be identified what factors that make an appraisal becomes effective and what obstructions that may appear. So the goal of performance appraisal should help employees to improve their performance, and with the available system it should produce active involvement from all parties that are exist in the organization whom are influenced by appraisal activity. Keywords: performance appraisal, effective appraisal, employee involvement, evaluation